Essay Writing as a Method of Developing Critical Thinking in a Foreign Language Class at Universities - Gafurova Norjon Nematovna (Genius Journals, 2022)
This article discusses the peculiarities of essay writing as a method of developing critical thinking in a foreign language class at universities and essay writing helps to learn how to work effectively with information, structure it, filter out questionable data, draw conclusions, solve problems and make the right decisions in a new situation.
Keywords: Critical Thinking; Creative; Writing; Skills